UI/UX Design of Psychology Consultation System Application Using the Design Thinking Method - Ahmad Taufiq Rohman; Joko Sutopo (Jurnal Indonesia Sosial Teknologi, 2024)
Mental health is an important issue facing the global community today. Every year, millions of people are affected by a variety of mental disorders, making mental health a very pressing issue. The study highlights the need for a mobile app-based psychological consultation system, which can provide better access for individuals experiencing mental problems. Through the design and development of effective systems, this research aims to understand how these apps can help individuals overcome mental health challenges, improve their quality of life, and facilitate better interactions between mental health professionals and users. This research method follows a design thinking approach to design UI/UX for psychology consultation system applications. This approach was chosen because it can produce more innovative solutions by understanding user needs in depth. From the results of this study, it is clear that the application of a psychology consultation system designed with a user-based approach can not only increase satisfaction but also increase user engagement. These findings support the initial hypothesis that a deep understanding of user needs can lead to better and more effective app designs.